Time course of the interaction between oral short-term ritonavir therapy with three factor Xa inhibitors and the activity of CYP2D6, CYP2C19, and CYP3A4 in healthy volunteers - Rohr, Brit Silja; Krohmer, Evelyn; Foerster, Kathrin; Burhenne, Jürgen; Schulz, Martin; Blank, Antje; Mikus, Gerd; Haefeli, Walter E. (Clinical pharmacokinetics, 2024)
We investigated the effect of a 5-day low-dose ritonavir therapy, as it is used in the treatment of COVID-19 with nirmatrelvir/ritonavir, on the pharmacokinetics of three factor Xa inhibitors (FXaI). Concurrently, the time course of the activities of the cytochromes P450 (CYP) 3A4, 2C19, and 2D6 was assessed.
Gesehen am 18.02.2025